Maturity Level for IT Implementation Measurement Focus on Business Goal 14 and 15 at Diskominfo Province - Mukaromah, Siti Mukaromah; Eva Y Puspaningrum; Doddy Riddwandono (IJCONSIST JOURNALS, 2021)
How Information Technology and Information System (IT/IS) has been implemented at an organization or institution needs to measure to evaluate IT/IS implementation. Nowadays, IT is compulsory in business processes. It helps the employee to handle some of their duty. But it needs to measure to monitor how IT/IS aligns with the business. So, that management could decide whether IT/IS is maintained or need to be upgraded or else. There are many ways to measure IT/IS implementation; this article will discuss the maturity level based on Cobit 4.1. It will measure per level from level 0 to level 5. The scope of this research is at business goal 14 and business goal 15 and a case study of this research in Diskominfo at one of the provinces in Indonesia. The result of this research is the maturity level of Business Goal 14, and Business Goal 15 is in Level 3, it means that Define Process.